OPTIMALISASI LITERASI MEMBACA PADA MAHASISWA NONBAHASA DENGAN METODE PAGITUKUL (PASANGAN-BERBAGI-WAKTU-PUKUL) - Fatin, Idhoofiyatul (Universitas Negeri Surabaya, 2016)
Students have different characteristics. These differences in characteristics can lead to the formation of learning groups that have similarities in learning styles. Non-graduate students such as Accounting and Health Analysts have an auditory learning style that likes lecture methods. The lecture method is not a bad method, but there is another method that can optimize reading literacy before the lecture method is used as a reinforcement of student understanding. This is necessary because literacy is the key to the formation of other types of literacy. The method that can optimize reading literacy is the Pagitukul (Pair-Sharing-Time-Punch) method which is a modification of the cooperative Learning-Shared-Pair-Share and Time-Pair-Co-op method. With the method is expected students do not expect and be empty glass that always filled by lecturers but students have a schematic of the material to be studied. After the application of the method to non-students, it is known that most students give positive response to Pagitukul method. Therefore, it can be said that Pagitukul method can be an alternative learning method that is able to optimize reading literacy in non-grammarian students.